Motorcycle in the West Java Province, Indonesia: Its Growth and Characteristics - Joewono, T.B.; Lauw, B.Z.; Hendy, H. (Civil Engineering Dimension, 2013)
Motorcycle provides several positive aspects in providing mobility, but its rapid increase in ownership and usage should be anticipated. The West Java Province has the highest number of population in Indonesia, which is potential to have the highest number of motorcycle. This study aims to develop a prediction model of motorcycle number and to develop a model of motorcycle ownership. Two models are proposed to predict the motorcycle growth in West Java, with gross regional domestic product and number of population as the independent variables. Four ordered probit models are proposed to explain motorcycle ownership in Bandung City based on economic, personal, user’s travel behavior, and motorcycle characteristics. This study explains that the increase of motorcycle ownership was not influenced by economic condition only, but also by travel behavior and their activity. Thus, besides economic aspects, the anticipation should also be based on travel and activity changes of the user.